TCL1A in naïve B cells as a therapeutic target for type 1 diabetesResearch in context - Siweier Luo; Lina Zhang; Chunfang Wei; Chipeng Guo; Zhe Meng; Honghui Zeng; Lele Hou; Le Wang; Zulin Liu; Yufei Du; Shiyu Tan; Yating Zhang; et al. (EBioMedicine)
Summary: Background: Type 1 diabetes (T1D) is an autoimmune disease characterised by the attack of pancreatic β cells by “self” immune cells. Although previous studies demonstrated that B cells contribute to T1D through antigen presentation and autoantibody production, the involvement of different populations of B cells, particularly in the early stages of T1D, has not been fully elucidated. Methods: In this study, we employed single-cell RNA sequencing (scRNA-seq) and flow cytometry to investigate immune cell populations in patients with newly diagnosed T1D, their relative controls and age-matched healthy controls. Phosphoprotein microarray analysis was employed to investigate changes in protein phosphorylation in B cells. Furthermore, we developed a siRNA-based nanomedicine and evaluated its therapeutic potential in the NOD mouse. The integration of scRNA-seq, flow cytometry, phosphoprotein microarrays, and functional assays established a robust framework for understanding and targeting B cell-mediated autoimmunity in T1D. Findings: Using single-cell RNA sequencing, we discovered that patients with T1D exhibited increased humoural immunity in the early stage of T1D. Specifically, the population of naïve B cells increased in patients with newly diagnosed T1D who expressed elevated levels of the AKT kinase coactivator TCL1A. Using a protein phosphorylation microarray, we confirmed that TCL1A knockdown specifically impaired AKT2 phosphorylation and affected B cell survival and proliferation. Notably, we discovered that the naïve B cell population increased and TCL1A expression was upregulated in NOD mice that developed T1D. Both the levels of naïve B cells and TCL1A were strongly associated with glucose intolerance in T1D mice. Importantly, treatment with a siRNA-based nanomedicine targeting Tcl1a mRNA effectively reduced the number of naïve B cells, prevented the loss of pancreatic β cells, and improved glucose intolerance in T1D mice. Interpretation: Using single-cell RNA-seq, we have not only uncovered a naïve B cell specific gene that may contribute to the pathogenesis of T1D but also highlighted the potential of siRNA-based nanomedicine for treating T1D. The clinical translation of these findings offers a new approach for the treatment of T1D. Funding: See Acknowledgements.